Outcome of in vitro fertilization in women with subclinical hypothyroidism - Cai, YunYing (Reprod Biol Endocrinol, 2017)
BACKGROUND: Previous studies examining associations between subclinical hypothyroidism (SCH) with in vitro fertilization (IVF) outcome indicate some benefits of levothyroxine (LT4) treatment. But IVF outcomes in treated SCH women whose serum Thyroid Stimulating Hormone (TSH) concentration did and did not exceed 2.5 mIU/L before the IVF cycle has not been studied thoroughly. METHODS: In this study, we performed a prospective cohort study with 270 treated subclinical hypothyroidism patients undergoing their first IVF retrieval cycle at a single cite. RESULTS: SCH in women receiving LT4 replacement with a basal TSH level between 0.2-2.5mIU/L displayed a similar rate of clinical pregnancy (47.4% vs 38.7%, P = .436), miscarriage (7.4% vs 16.7%, P = .379) and live birth (43.9% vs 32.3%, P = .288) compared to women with a basal TSH level between 2.5-4.2 mIU/L. CONCLUSION: Strictly controlled TSH (less than 2.5 mIU/L) before IVF may have no effect on the pregnancy rate in LT4 treated SCH women.